Theater in the Planned Society Contemporary Drama in the German Democratic Republic in its Historical, Political, and Cultural Context - Huettich, H.G (UNC Studies in the Germanic Languages and Literatures, 1978)
This study presents the historical development of topical drama in the German Democratic Republic from 1945 to 1975. The author investigates the sociopolitical function of both dramas and dramatists such as Karl Grünberg, Friedrich Wolf, and Erwin Strittmatter during the various transitional stages of the GDR's growth toward a socialist society. The substantive, critical study of plays, authors, productions, and dramatic theory is supplemented by a critical analysis of the Socialist Unity Party's cultural and literary policies during the GDR's turbulent history. While Western critics tend to isolate individual GDR dramas and interpret them out of context, Huettich explores in depth how the cultural policy of the GDR significantly helped shape the course of post-World War II drama in the 'planned society.'